2019
DOI: 10.21831/cp.v38i1.23164
|View full text |Cite
|
Sign up to set email alerts
|

A Learning Model of Bahasa Indonesia as a Foreign Language Based on Local Intercultural Politeness

Abstract: The study was aimed for developing a learning model of Bahasa Indonesia based on local intercultural politeness to improve the foreigners’ communicative competencies. This is Research and Development, started with a preliminary study of intercultural learning concepts and Buginese politeness strategies; the distribution of the needs analysis instruments to the 25 foreigners learning Bahasa Indonesia in Makassar, South Sulawesi, Indonesia; model development, focus group discussions; the model finalization and  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…Insufficient knowledge and understanding of Indonesian cultures, therefore, will give consequences to the learners to understand the richness of Indonesian people with their cultural varieties (Ruskhan, 2007). Gusnawaty & Nurwati (2019) reiterate the importance of moral values, i.e. speech politeness, in a teaching model internalizing the Indonesian local cultures.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Insufficient knowledge and understanding of Indonesian cultures, therefore, will give consequences to the learners to understand the richness of Indonesian people with their cultural varieties (Ruskhan, 2007). Gusnawaty & Nurwati (2019) reiterate the importance of moral values, i.e. speech politeness, in a teaching model internalizing the Indonesian local cultures.…”
Section: Discussionmentioning
confidence: 92%
“…The number of Indonesian learners in Victoria has now put the Indonesian language ranks four (Dodiangga, 2017) after Mandarin, Chinese, and Italian and it has been taught in 500 schools and it becomes the fourth most popular language in Australia (Andayani, 2016; cited in Gusnawaty & Nurwati, 2019). In addition, Backwell also shared some new views on the strategies to improve the quality of bilateral relationships between Australia and Indonesia in general and Australian schools and UPI in particular.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy used was the adaption of the word games poetry model being known since 1993. The third research was from Gusnawaty & Nurwati (2019) entitled "A Learning Model of Bahasa Indonesia as A Foreign Language Based on Local Intercultural Politeness". They found that the model was effective in overcoming the foreign learners' problems in oral interactions and improving their Indonesian language communicative competencies.…”
Section: Figure 1 Foreign Language Education Model By Byram and Esartementioning
confidence: 99%
“…All this information is important for developing a better T&LIFL program. The previous study done by Gusnawaty & Nurwati (2019) explored cultural aspects of T&LIFL but it was limited in term of local intercultural politeness. Therefore, this study intends to explore cultural aspects of T&LIFL in the broad sense.…”
Section: Figure 1 Foreign Language Education Model By Byram and Esartementioning
confidence: 99%
“…Teachers will be assisted in selecting and developing material of language course that is appropriate with the major styles and characteristics of the class, developing varieties and not-single learning methods, selecting activities that are suitable for students learning styles (Xu, 2011). This variation in students' ethnicities, in this case, is the tribes, according to Saddhono is actually the basis of multicultural class management method in learning (Gusnawati & Nurwati, 2018). Politzer & McGroarty of their study on investigating Asian and Hispanic students then theorize that ethnicity might have a strong influence on some effective strategies employed by students (Ghani, Khairisman, & Samad, 2016).…”
Section: Introductionmentioning
confidence: 99%